Does the presence of unilateral gingival recession on maxillary canines influence smile esthetics? - Figueiredo,Bruna Alecrim (2020)
ABSTRACT Objective: The objective of this study was to determine orthodontists’, periodontists’, and laypersons’ perception of smile esthetics, regarding the presence of different levels of gingival recession on the maxillary left canine. Material and Methods: Two close-up smile images (frontal and oblique) of a white female were selected for this study. The images were digitally altered to create different levels of gingival recession on maxillary left canine, in 0.5-mm increments. They were randomly arranged into a photo album that was shown to 135 evaluators: 45 orthodontists, 45 periodontists, and 45 laypersons. Each evaluator was asked to rate the smile attractiveness, using to a visual analog scale. Data were analyzed statistically using ANOVA, Tukey’s post-hoc test, and Student t-test. Results: According to the orthodontists and periodontists, all levels of recession were considered as unesthetic in both types of images. According to the laypersons, gingival recession > 1.5 mm in the frontal image and > 1.0 mm in the oblique image were considered unesthetic. Conclusion: The results showed that the presence of unilateral gingival recession on maxillary canines may negatively influence smile attractiveness, depending on the evaluator type and the level of the recession.